Thematic Analysis of the Concept of Piety in the Qur'an and Its Application to Character Education in the Islamic Boarding School Environment - Mohammad, Shafwatun Nada; Rifky, Mohammad; Rhain, Ainur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This research aims to analyze the concept of piety in the Qur'an and its application in character education in Islamic boarding schools. The method used is a qualitative approach with an analytical descriptive research design, which examines the literature and interpretation of the Qur'an related to piety and its application in Islamic boarding schools. Data were collected through the analysis of texts related to piety and literature studies related to piety based character education. The results of the study show that piety in the Qur'an includes spiritual, moral, and social dimensions, which are reflected in real behavior. The application of piety values in pesantren education has proven to be effective in shaping the character of students, both in personal and social aspects. The study also found that pesantren integrate pious values into their curriculum, through religious and social teaching activities that emphasize social awareness and responsibility. The conclusion of this study is that piety has a central role in the formation of the character of students, which can be applied in various aspects of life. This research makes an important contribution in the field of Islamic education, especially in the development of Qur'an-based character education